ИМПЛЕМЕНТАЦИЈА НА ОПТИМИЗАЦИЈАТА НА МЕДИЦИНСКАТА ЕКСПОЗИЦИЈА ВО КЛИНИЧКАТА ПРАКСА НА ИНСТИТУТОТ ЗА РАДИОЛОГИЈА, СКОПЈЕ, МАКЕДОНИЈА - Nikolova, Sonja (My University, 2019)
Radioactivity is a natural phenomenon and feature of the environment. Radiation and radioactive substances have many beneficial applications, ranging from power generation, to uses in medicine, industry and agriculture.In recent years, new radiology technologies and devices using ionizing radiation, such as CT and PET-CT, have led to major improvements in the diagnosis and treatment of various diseases. However, inappropriate or unskilled use of such technologies and devices can lead to unnecessary or unintended man-made radiation exposures and potential health hazards to patients and staff.According to the IAEA ( International Atomic Energy Agency), all medical exposures should be guided by the general principles of radiation protection which include-justification, optimization and dose limit. Regulation is essential to control radiation exposure in clinical practice.Optimization of medical exposure means that all exposure should be kept as low as can be rationally achieved, taking economic and social factors into consideration. Optimization is considered from the viewpoints of image quality and exposure reduction which was the main purpose of our project-to possibly reduce the exposure in 100 CT scans and 100 chest x-rays without losing the diagnostic quality of the images that were acquired. We were collecting information about the total doses of exposition prior to, and after the optimization, and image quality estimation, in order to prove the benefit of optimization in medical exposure.Although dose limits for medical exposure have not been established by law, it is necessary to confirm the potential benefit for the patient from medical exposure of radiation, balanced by the potential risks.
IMPLEMENTING OPTIMISATION OF MEDICAL EXPOSURE IN CLINICAL PRACTICE AT THE INSTITUTE OF RADIOLOGY, SKOPJE, MACEDONIA
Keywords: radioactivity; optimization; medical exposure